KEWENANGAN JAKSA DALAM PENERAPAN SANKSI PIDANA MATI TERHADAP PELAKU TINDAK PIDANA PENYALAHGUNAAN NARKOTIKA - Roceberry Ceristanthy Damanik; T. Erwinsyahbana (JURNAL DOKTRIN REVIEW, 2022)
The application of capital punishment to perpetrators of narcotics abuse which is under the authority of the Prosecutor as law enforcer, found obstacles related to the mechanism for implementing capital punishment which makes it difficult to carry out death penalty executions. The role and authority of theProsecutor in carrying out criminal law enforcement, according to Article 1 Paragraph (1) of the Prosecutor's Law, namely the Prosecutor is a functional official who is authorized to act as a Public Prosecutor and to Implement Court Decisions. Prosecutors to apply the death penalty for perpetrators of narcotics abuse in accordance with Article 270 of the Criminal Procedure Code Prosecutors are the Executors of Court Decisions that have obtained permanent legal force. and The procedure for executing capital punishment is explained in Perkap No. 12 of 2010 concerning Procedures for the Implementation of Death Penalties, as well as the factors that influence the implementation of the Prosecutor's authority to apply death penalty for perpetrators of narcotics abuse are First the legal factor itself, Second the law enforcement factor, Third the means of law enforcement, Fourth the community factor, Fifth cultural factors. Therefore, the Government should make a new regulation that provides a solution so that death row convicts do not try to find ways to delay the execution.